Implementation of Akad Salam in the Practice of Buying and Selling Red Bricks in Sumberingin Kulon Village - Reni Waningsih; Binti Nur Asiyah (CV. Syntax Corporation Indonesia, 2024)
Salam buying and selling is an agreement to buy and sell ordered goods between a seller and a buyer with the specifications, price and order time agreed at the beginning of the contract, and payment is made in full in advance. This research aims to determine the implementation of the salam contract in the practice of buying and selling red bricks in Sumberingin Kulon village.. The approach used is a qualitative approach with descriptive methods. Data collection techniques in this research used observation, interviews and documentation. The results of this research show that the implementation of the greeting contract has been implemented in the practice of buying and selling red bricks in Sumberingin Kulon village.